Introduction To Higgs Sector: Theory and Phenomenology - Demir, Durmuş Ali; Demir, Durmuş Ali (Springer Verlag, 2008)
This review is based on lectures delivered at International Summer School on High Energy Physics, in Akyaka, Mugla, Turkey, September 2006. The goal of the review is to introduce junior graduate students, having a some knowledge of field theory, to the problem of mass generation and its physical consequences. The review starts with the statements and a toy model of mass generation in Sect. 2. In Sect. 3 a model of weak interactions is constructed and its predictions are compared with experimental results obtained so far. Given in Sect. 4 is search strategies for Higgs boson, the only remnant of the mechanism that gives mass to matter, by referring to model predictions and experimental facilities. Finally, in Sect. 5, given are a summary of results plus reasons for and expectations from models which rehabilitate the minimal model constructed in Sect. 3.
Proceedings of the 2nd International Summer School in High Energy Physics, Muğla, 25–30 September 2006
Keywords: Particles(Nuclear physics); Mass generation; Electroweak theory; Higgs field